Analysis of Movies Product Placement and its Effect Toward The Audiences (Case Study: Ayat-Ayat cinta, Perahu kertas, Habibie & Ainun) - Subianti, Tripuspa; Hudrasyah, Herry (Journal of Business and Management, 2013)
The weariness of audience in watching commercial during their favorite TV shows at home is one of the reasons product placement was born in the marketing world.Ã‚Â Nowadays, product placement is something familiar on the television program shows and feature movies. According to Balasubramanian (1994) product placement is hybrid messages include all paid attempts to influence audiences for commericial benefit using communications that project a non-commercial character; under these circumstances, audiences are likely to be unaware of the commercial influence attempt and/or to process the content of such communications differently than they process commercial messages. Morover Wiles (2009) states product placement in movie is an investment for brands trying to reach a niche audience and there are strong reasons for investors to expect that film product placement will increase consumer awareness of a particular brand. A big-budget feature film that has expectations of grossing millions may attract many commercial interests; however, the film studio must also analyze if a product fits with the image of the film. A high-profile star may draw more attention to a product, and therefore, in many cases, this becomes a separate point of negotiation within his or her contract. In Indonesia, product placement in movies is starting to grow due to the catalyst work of the film makers that think that they can cooperate with commercial companies to obtain benefits for both parties. A company can help cover up the cost of film production while the director can provide space to hold corporate product placement in movies. However, both parties must have an appropriate strategy to achieve the balance between keeping the quality of the movie and still delivering an effective product placement. The effectiveness of product placement in movie can be measured using brand recall, and includes the factors of product familiarity, program involvement (arousal, pleasure, cognitive effort), and high-profile star/star liking. This study used an explorative and descriptive design. Explorative is used to gain data from the key informants, which will be analyzed and compared with literature study. Descriptive design is used to measure the effectiveness of product placement in movie from the audiences aside. By using three commercial movies directed by Hanung Bramantyo whichÃ‚Â is a famous director who received numerous awards and made several successful commercial movies in IndonesiaÃ‚Â titled Ayat - Ayat Cinta, Perahu Kertas, and Habibie & Ainun as objects of the research, moreover these movie based on best-seller novel, this paper discusses product placement that occured on all three movies and its effect toward the audiences, which in turn can be an input and evaluation materials to directors and producers in Indonesia, particularly Hanung Bramantyo in making commercial movie in the future. Ã‚Â Key Words: Product Placement in Movie, Product Placement, Brand Recall